Measurement Of Right Lobe Of Human Liver By Ultrasound And Correlation With Age And Bmi Of Individuals (Journal of Pharmaceutical Negative Results, 2022)
The liver is largest abdominal organ, occupying the upper portion of abdominal cavity. It occupies most of the right hypochondrium and epigastrium, and frequently extends into the left hypochondrium as far as the left anterior axillary line. On the diaphragmatic surface, the liver is divided into two lobes, right and left, by the attachment of the falciform ligament. The right lobe which forms the base of the wedge-shaped liver is approximately six times larger than the left lobe. On the visceral surface, the liver is divided into four lobes:(a) right lobe, (b) left lobe, (c) quadrate lobe, and (d) caudate lobe by fissures and fossae present on this surface(fissures for ligamentum teres and ligamentum venosum ,porta hepatis, groove of the IVC and fossa for the gall-bladder). These fissures and fossae form an H-shaped figure.(a) Right lobe to right of the fossa for gallbladder.(b) Left lobe to the left of the fissures for ligamentum teres and ligamentum venosum.(c) Quadrate lobe, between the fossa for gallbladder and the fissure for ligamentum teres below the porta hepatis.(d) Caudate lobe, between the groove for IVC and the fissure for ligamentum venosum above the porta hepatis.As the size of body grows the liver rapidly increases in its size. This period of growth reaches its peak around 18years and is followed by a gradual decrease in liver weight from middle age.